Microscydmus trianguliceps Franz and Pseudoeudesis sulcata Franz transferred to Afroeudesis Franz (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2016)
Afroeudesis Franz was described as a subgenus of Pseudoeudesis Binaghi (Scydmaenini), with a single species from Tanzania. Recently, Afroeudesis was transferred to Glandulariini and elevated to generic rank, and the sub-Himalayan Nanoscydmus Jałoszyński was reduced to a subgenus of Afroeudesis. New surprising findings concerning Afroeudesis are presented here, extending the known geographic range of this enigmatic genus. Microscydmus trianguliceps Franz (Ivory Coast) and Pseudoeudesis sulcata Franz (SE Brazil) are transferred to Afroeudesis, each to a newly established subgenus: Eburneus subgen. n. and Eudesoides subgen. n., respectively. Afroeudesis (Eburneus) trianguliceps comb. n. and Afroeudesis (Eudesoides) sulcata comb. n. are redescribed. The genus name Eudesis is interpreted here as feminine; consequently Afroeudesis (Nanoscydmus) baoshanus is corrected to baoshana. The disjunct and possibly relict Gondwanan distribution of Afroeudesis is discussed.